Electric field effect on polar nanoregions of uniaxial ferroelectric SrxBa1−xNb2O6 with weak random fields studied by Brillouin scattering. (1st May 2018) - Aftabuzzaman, Md; Dec, Jan; Kleemann, Wolfgang; Kojima, Seiji
Abstract: The electric field effects on the acoustic properties of uniaxial ferroelectric Sr x Ba1− x Nb2 O6 ( x = 0.40, SBN40) crystals with weak random fields were studied by Brillouin scattering. On field cooling, the minimum of longitudinal acoustic (LA) velocity shifted to a higher value and a marked increase in LA velocity was observed below the Curie temperature T C . This signifies the enhancement of the long-range ferroelectric order due to the alignment of polar nanoregions (PNRs) along the field direction. After poling the crystal with a high electric field for 60 min above T C, the alignment of all PNRs along the field direction was observed. By decreasing the poling time, LA mode splitting was observed below T C owing to the back switching of PNRs. In a field-dependent measurement below T C, a mixed state consisting of macro- and nanodomains persisted up to a very high electric field because of the incomplete switching of nanodomains due to the interaction among PNRs.